2006
DOI: 10.1097/01.wnf.0000236766.08409.03
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam in the Prophylaxis of Migraine With Aura

Abstract: Levetiracetam seems to be a safe and effective treatment for migraine with aura. Controlled trials are needed to confirm the observed results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 14 publications
4
61
0
5
Order By: Relevance
“…Less evident is the efficacy of preventive therapy with levetiracetam in migraine [Cochran, 2004;Miller, 2004;Brighina et al, 2006]. In animal models, levetiracetam contrasts to reference AEDs by its ability to antagonize neuronal (hyper)synchronization in the highly seizure-prone CA3 area of rat hippocampal slices [Margineanu and Klitgaard, 2000].…”
Section: Levetiracetammentioning
confidence: 97%
“…Less evident is the efficacy of preventive therapy with levetiracetam in migraine [Cochran, 2004;Miller, 2004;Brighina et al, 2006]. In animal models, levetiracetam contrasts to reference AEDs by its ability to antagonize neuronal (hyper)synchronization in the highly seizure-prone CA3 area of rat hippocampal slices [Margineanu and Klitgaard, 2000].…”
Section: Levetiracetammentioning
confidence: 97%
“…Эффективность леветирацетама в профилактиче-ском лечении мигрени была показана в небольшом от-крытом исследовании, проведенном Brighina с колле-гами [4], в котором пациенты получали леветирацетам в дозе 1000 мг/сут в течение 6 месяцев. Авторы пока-зали, что леветирацетам обычно хорошо переносится и эффективен при лечении мигрени.…”
Section: леветирацетам и гипералгезияunclassified
“…Limited information from retrospective and open label trials suggests that levetiracetam may have utility in migraine prophylaxis (Drake et al, 2001;Krusz, 2001a;Cochran, 2004;Miller, 2004;Rapoport et al, 2005;Vaisleb et al, 2005;Brighina et al, 2006). Levetiracetam has been marketed for epilepsy therapy since 2000, but its molecular target in brain was only recently identifed (Lynch et al, 2004).…”
Section: Levetiracetammentioning
confidence: 99%
“…Evidence from double blind randomized placebo-controlled studies also support the effectiveness of gabapentin in migraine prophylaxis (Di Trapani et al, 2000;Mathew et al, 2001) and it is considered a third line agent by BASH. Less robust clinical studies have indicated that carbamazepine (Rompel et al, 1970), lamotrigine (Steiner et al, 1997;D'Andrea et al, 1999;Lampl et al, 2005;Gupta et al, 2007), zonisamide (Drake et al, 2004;Pakalnis and Kring, 2006) and levetiracetam (Brighina et al, 2006) may also be effective in the treatment of migraine. A metaanalysis by the Cochrane Collaboration confirmed that as a class AEDs reduce migraine frequency and are relatively well tolerated (Chronicle and Mulleners, 2004).…”
Section: Introductionmentioning
confidence: 99%